Influência do paleoclima e clima atual nos padrões de diversidade beta taxonômica, funcional e filogenética de anfíbios anuros do Cerrado - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Recent studies have tried to understand the contribution of past climatic variation and current climate to determine variation in species composition (beta diversity). Approaches that include not only taxonomic beta diversity (TBD), but also functional (FBD) and phylogenetic diversity (PBD), may be complementary since each type of measure may reflect the influence of the current or past climatic variables. In addition, beta diversity can be decomposed into turnover (turn) and difference of richness (diff), which may explain different processes such as specialization to environmental gradients or selective extinctions due the action of environmental filters. In this study, we tested the relative influence of current climate and climatic variation along the last glacial maximum, average Holocene and current climate on the components of turnover and difference of richness in TBD, FBD and PBD in anuran communities in the Cerrado. We compile anuran inventories in the Cerrado, current and past climatic variables for the same localities. Based on the recorded species, we compiled its phylogenetic relationships and its functional traits. We calculated the components of turnover and difference of richness, as well as the contribution of local beta diversity (LCBD) for TBD, FBD and PBD. We use the distance-based RDA and the variation partition to test the relative influence of space, current climate and paleoclimatic stability on TBD, FBD and PBD (turn and diff). The influence of climatic and paleoclimatic variables on LCBDs was tested using the generalized regression of least squares and a model selection approach. The turnover component was more explained by the climate in conjunction with the space in TBDturn and PBDturn, while in FBDturn the climate and paleoclimatic variation were more explanatory. The LCBDs of TBD, TBDturn, PBD, PBDturn and FBDdiff were negatively related to the paleoclimatic variation of the annual mean temperature. However, the LCBD presented negative relationship with the palaeoclimatic variation in the raining of the driest month for DBF and positive relation with the same variable for DBFdiff. These results demonstrate the relation of the functional traits with the precipitation, since the anurans are animals that have a great dependence of the water for its activities and this differentiation in the functional traits in some communities is due to the addition of species from humid biomes adjacent to the Cerrado.
Keywords: Anura; Beta diversidade; Traços-funcionais; Filogenia; Savana; Anura; Beta diversity; Functional traits; Phylogeny; Savanna; CIENCIAS BIOLOGICAS